How Important is Having Skin in the Game? Originator-Sponsor Affiliation and Losses on Mortgage-backed Securities - Demiroglu, Cem; James, Christopher (Review of Financial Studies, 2012)
This article examines the relationship between a mortgage originator's affiliation with the sponsor of a securitization or the servicer of the securitized loans and the default rate on the securitized mortgages. We find that default rates are significantly lower for securitizations in which the originator is affiliated with the sponsor or servicer. Consistent with investors expecting performance to vary with affiliation, we find that the initial yields on mortgage-backed securities (MBS) are lower and the percentage of AAA-rated securities issued against the securitized pool of loans is higher when the originator is affiliated with either the sponsor or servicer.